1992
DOI: 10.1099/00222615-37-2-123
|View full text |Cite
|
Sign up to set email alerts
|

Motility as a factor in the colonisation of gnotobiotic piglets by Helicobacter pylori

Abstract: Summary. Non-motile variants of Helicobacterpylori (strain 26695) occurred with a frequency of 1.6 (SD 0.4) x lo-* variants/cell/division cycle, and reversion to the motile form occurred with a frequency of < lo-' variants/cell/division cycle. The two forms remained > 90 YO pure for up to 50 cell divisions and differed only in the presence or absence of motility and flagella. Bacteria were recovered from nine of 10 gnotobiotic piglets inoculated orally with motile H. pylori, but from only two of eight inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
248
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(258 citation statements)
references
References 12 publications
6
248
0
2
Order By: Relevance
“…The observation that urease binds to class II MHC on gastric epithelial cells may help explain why urease-negative mutants of H. pylori failed to colonize in an animal model of infection even under hypochlorhydric conditions (6). In other studies with ureasenegative mutants, it was speculated that the failure to colonize was due to a requirement of the enzymatic activity to provide a more hospitable environment for H. pylori to grow (5,36).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The observation that urease binds to class II MHC on gastric epithelial cells may help explain why urease-negative mutants of H. pylori failed to colonize in an animal model of infection even under hypochlorhydric conditions (6). In other studies with ureasenegative mutants, it was speculated that the failure to colonize was due to a requirement of the enzymatic activity to provide a more hospitable environment for H. pylori to grow (5,36).…”
Section: Discussionmentioning
confidence: 96%
“…Isogenic mutant H. pylori strains showed that urease is essential for colonization because the mutant bacteria were unable to colonize gnotobiotic pigs (5). However, the urease-negative H. pylori strains also failed to colonize under hypochlorhydric conditions (6), which suggested a role for urease in colonization beyond its ability to neutralize the gastric acidity.…”
mentioning
confidence: 99%
“…typhimurium (Jones et al, 1992;Khoramianfalsafi et al, 1990), Helicobacter pylori (Eaton et al, 1992), and Bacillus thuringiensis (Zhang et al, 1993). With regard to plant pathogens, correlations between chemotaxis, motility, and virulence were found for Xanthomonas campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the enhancement of the urease activity on the surface of H. pylori by binding with pre-administrated S3 MAb secreted from gastric mucosa may augment the ability to colonize onto the gastric mucosa through association with the class II MHC molecules expressed on the gastric epithelial cells (10,11). Indeed, there are a number of reports showing that H. pylori urease expressing outside of the bacteria seems to be a critical factor for adhering to the gastric mucosa and urease-negative H. pylori strains as well as the urease mutants failed to colonize the gastric compartment (6,8).…”
Section: Figmentioning
confidence: 99%